Penerapan Pendekatan Culturally Responsive Teaching (CRT) Dalam Pembelajaran Menulis Teks Deskripsi - Hera Fasirah; Sakinah Fitri (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to improve the ability to write descriptive texts by applying the Culturally Responsive Teaching (CRT) approach. The type of research used in this study is Classroom Action Research. The subjects of this study were students of class VII-3 SMP Negeri 24 Makassar totalling 36 people. The research instrument used in this study was a performance test. The research data were analysed using descriptive statistics. The results of the study found that the completeness of learning outcomes of Makassar culture-based writing that in cycle 1 with an average of 35% while cycle 2, experienced an increase with an average value to 83%. Based on this, it can be concluded that the Culturally Responsive Teaching (CRT) approach is effectively used in improving the ability to write description text.